The Creative Efforts of the Arra’Sye Pelayangan Community in Promoting and Developing the Arab-Malay Zapin Dance in Jambi City - Cynthia Pahni Maharani; Eva Riyanti; Adjuoktoza Rovylendes; Syielvi Dwi Febrianty (Melayu Arts and Performance Journal, 2025)
This study examines the creativity of the Arra’sye Pelayangan community in developing the Arab-Malay Zapin dance in Jambi City. The Arab-Malay Zapin is a performing art resulting from the cultural interaction between Arab and Malay traditions, carrying strong historical, aesthetic, and religious values within the Pelayangan community. The aim of this research is to analyze the creative strategies employed by the community to preserve and further develop the dance so that it remains relevant within contemporary cultural contexts. This study utilizes a qualitative approach with data collected through interviews, observation, and documentation. The analysis is based on theories of creativity and dance form. The findings show that the Arra’sye Pelayangan community has introduced innovations in movement structure, floor patterns, musical accompaniment, costumes, and performance presentation while maintaining the authenticity of traditional values. The community also ensures regeneration through regular training and by involving local youth in various performances. Additionally, contemporary adaptations in aesthetics and staging are implemented to enhance the appeal of the dance to younger audiences. These creative efforts demonstrate that traditional performing arts can continue to grow through a balanced approach that integrates cultural preservation with contemporary artistic needs.